Schottky-MOS Hybrid Anode AlGaN/GaN Lateral Field-Effect Rectifier With Low Onset Voltage and Improved Breakdown Voltage - Gao, Jingnan; Wang, Maojun; Yin, Ruiyuan; Liu, Shaofei; Wen, Cheng P.; Wang, Jinyan; Wu, Wengang; Hao, Yilong; Jin, Yufeng; Shen, Bo (IEEE ELECTRON DEVICE LETTERS, 2017)
For devices with a 15 micron anode-to-cathode distance, nearly 1.5 times increase in the blocking (breakdown) voltage (from 692 to 1030 V) has been achieved by replacing the alloyed Ohmic contact at the anode electrode of the conventional MOS gated hybrid-anode lateral field-effect rectifier (CMLFER) with a low barrier Schottky contact. The new Schottky-MOS hybrid-anode lateral field-effect rectifier is found to offer comparable low onset voltage (V-ON of 0.68 +/- 0.13 versus 0.65 +/- 0.11 V for CMLFER) independent of the anode-to- cathode distance. The immunity of the punch through caused by drain induced barrier lowering effect is obtained through the low barrier Schottky contact in anode, which is believed to be responsible for the reduction in the leakage current, and the improvement of rectifier breakdown voltage.